Acceleration of NLRP3 inflammasome by chronic cerebral hypoperfusion in Alzheimer's disease model mouse. (June 2019) - Shang, Jingwei; Yamashita, Toru; Zhai, Yun; Nakano, Yumiko; Morihara, Ryuta; Li, Xianghong; Tian, Feng; Liu, Xia; Huang, Yong; Shi, Xiaowen; Sato, Kota; Takemoto, Mami; et al.
Graphical abstract: Chronic cerebral hypoperfusion (CCH) strongly exaggerated Aβ accumulations. CCH greatly exacerbated neuroinflammation and NVU dissociation in AD mice. Primary AD pathology was greatly protected by galantamine. Highlights: Chronic cerebral hypoperfusion (CCH) strongly exacerbated neuroinflammation. CCH greatly exaggerated Aβ accumulations and NVU dissociation in AD mice. CCH induced AD pathology which was greatly protected by galantamine. Abstract: Cerebral neuroinflammation defines a novel pathway for progressing Alzheimer's disease (AD) pathology. We investigated immunohistological changes of neuroinflammation with nucleotide-binding domain and leucine-rich repeat (NLR)-protein 3 (NLRP3), activated caspase-1 and interleukin-1 beta (IL-1β) in a novel AD (APP23) mice with chronic cerebral hypoperfusion (CCH) model from 4 months (M) of age, moreover, examined protective effect of galantamine. CCH strongly enhanced NLRP3, activated caspase-1 and IL-1β expressions in hippocampus and thalamus at age 12 M of AD mice. CCH also exaggerated amyloid-beta (Aβ) 40 depositions in cerebral cortex. Furthermore, CCH exacerbated a marked dissociation of neurovascular unit (NVU). These pathological changes were ameliorated by galantamine treatment. The present study demonstrated that CCH strongly enhanced primary AD pathology including neuroinflammation, Aβ accumulations and NVU dissociation in AD mice, which was greatly protected by an allosterically potentiating ligand galantamine.